Elements for the success of organizational transformations: A theoretical discussion (GEON Journal (Management, Organizations and Business), 2024)
Problematic. The complexity of organizational change, driven by global competition and technology, has led to prioritizing projects to enhance business performance. However, only 20-30% of these projects are successful, especially in organizational transformations, where only 25% achieve positive short- and long-term results. The COVID-19 pandemic exacerbated this situation, forcing disruptive adaptations in companies. objectives The purpose of this article is to theoretically discuss the elements for the success of organizational transformations based on the 10-element Model. Materials and methods Qualitative in nature, supported by an interpretative inquiry process in international databases for the analysis of different categories and subcategories of the model's components. The research was based on an exploratory-descriptive scope that served to specify which elements are most developed by the literature in the framework of project formulation and execution and what possible variables should be considered in project management. Results. Among the main elements of the model, it was found that the most significant ones were Committed Leadership, Governance, Change Culture, and Change Vision. Discussion Based on the theoretical review, future analysis subcategories could include elements such as agile methodologies, risk management, and innovation, which would strengthen their configuration and application in the organizational context. Conclusions. It is concluded that there is no consensus, let alone models that articulate technical criteria or factors with human ones, but there is a need to evaluate project results not only in terms of success or failure but also considering different backgrounds and causes. Contribution / originality Incorporating agile methodologies in project management as a key variable in the model means moving away from a single and rigid approach to a flexible one, adapting to the specific needs of each project, and considering collaboration and adaptability in its development.
Keywords: projects, management, change, transformation, organizational, leadership